The Impact of Foreign Aid on Local Development: A Grid Cell Analysis - Bitzer, Jurgen; Goren, Erkan (The Journal of Development Studies, 2024)
We examine whether geocoded World Bank foreign aid projects affect economic activity at the level of equally sized grid cells with a spatial resolution of 0.5 decimal degrees latitude and longitude. We use geospatial data for 58,676 grid cells during the period 1997-2013 with about one million grid-by-year observations. Using fixed effects estimating techniques, we evaluate the impact of World Bank foreign aid projects on grid cell night-time light growth. The estimates reveal that World Bank foreign aid projects contribute significantly and positively to grid cell economic activity measured by night-time light growth. We complement the fast-growing literature using geocoded data to assess aid effectiveness at the subnational level. We provide evidence that the lack of robust empirical findings at the country and subnational (e.g., ADM1 and ADM2) level can be explained due to spatial aggregation and the choice of spatial units. Additional estimates and robustness tests further corroborate our main findings.
Keywords: Aid Effectiveness; Geocoded Foreign Aid Projects; GIS Data; Grid-Cell Analysis; World Bank; Economic Growth